(untitled) (Advancements in Homeopathic Research, 2022)
Abstract Allergic skin affections are burning issue now days. Urticaria is one of such allergic dermatological affection that is seen worldwide and may be present at any age.Inspite of taking conventional therapies recurrence rates are high. Homoeopathic internal medication is useful in such local maladies. Up till now very few experiments are done on use of LM potency so, this study was selected to work on. Aims & Objective: To see the efficacy of homoeopathic medicines prescribed in LM potency in cases of Urticaria. Methodology 30 pre-diagnosed cases or cases with clinical presentation of Urticaria were randomly selected irrespective of age and sex. Medicines were selected on reportorial as well as non-reportorial base depending upon the demand of the case. In every case medicines were given in LM potency which was raised in ration of 0/1, 0/3, 0/6, 0/9 etc. as per need. Results Among 30 cases of urticaria 12 were acute and 18 were chronic cases. 90% cases responded well i.e. 60% were cured and 30% cases were improved. 10% cases did not improve.Out of 12 acute cases, 10cases were cured, 1improved and 1 did not improve.Out of 18 chronic cases 08 cases were cured, 8 were improved and 2 cases did not improve. Medicines in LM potency ranging 0/1 to 0/3were found most useful in acute urticaria while in case of chronic urticaria 0/1 to 0/6 LM potency found most useful. Conclusion The findings of this study suggest that homoeopathic medicines prescribed in LM potency were effective in managing acute as well as obstinate chronic cases of urticaria.